Najib al-Kailani's Social Criticism in the Novel "Ahl al-Humaidiyah" - Jaidah , Elvia (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The purpose of this research is to analyze the forms of social criticism in the novel Ahl al-Humaidiyah (People of Humaidiyah) by Najib al-Kailani. This research use a sociology of literature approach with a focus on the theory of social criticism. The method used is descriptive-qualitative, with data collection carried out through close reading and note-taking of textual excerpts containing social criticism. The data are analyzed by identifying social issues within the text and interpreting the social criticism conveyed by the author through characters, conflicts, plot, and dialogue. The results show that the novel contains various forms of social criticism, including criticism of social class differences, nepotism in education, abuse of power, misuse of political ideology, and patriarchal views that disadvantage women. Through the depiction of conflicts, characters, and events in the story, al-Kailani conveys criticism of various social issues while emphasizing the importance of justice, equality, and social responsibility in social life. In this regard, the novel Ahl al-Humaidiyah functions not only as a literary work but also as a medium for conveying social criticism of societal conditions.